Determination of nutrient composition and presence of bacteria in raw versus boiled chicken liver diet - Tan, K. N.; Megat Abdul Rani, Puteri Azaziah; Abu Hassim, Hasliza; Bejo, Siti Khairani (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
The purpose of this study was to determine the nutrient composition and presence of bacteria in both raw and boiled chicken livers. A total of six samples for each raw and boiled chicken livers, were prepared for the nutrient composition analysis. Both samples were also prepared for bacteria isolation and identification. All samples were cultured on the blood agar and tryptic soy agar for bacteria isolation. The isolated bacteria were identified using biochemical tests. Result shows that all proximate analysis for moisture content, dry matter, crude fat and crude protein, were statistically difference between raw and boiled chicken liver, except for ash content percentage. The bacteria species isolated from raw chicken livers were Aeromonas species, Streptococcus species, Actinomyces species, Proteus mirabilis and Salmonella species. There was absence of viable bacteria isolated from boiled chicken livers. Thus, it can be concluded that the raw chicken liver contains higher nutrients composition but harbours numerous opportunistic bacteria that might compromise the general health in pets as well as to the public.